Autonomy and the instrumental music teacher: negotiating culture in professional practice. Issue 1 (2nd January 2020) - Boyle, Kerry
ABSTRACT: This study provides valuable insights concerning the nature of professional practice in instrumental teachers working in a range of professional contexts in the UK. Using Bourdieu's conceptual tools of habitus, field and capital, the analysis explores the way in which individuals negotiate the field of instrumental music education, revealing high levels of professional autonomy and specific understandings of the role of the contemporary professional musician. The findings demonstrate the extent to which musicians' understandings and practices are culturally determined and perpetuated, highlighting the relationship between specific aspects of the field of instrumental teaching and learning and understandings of professional identity. The perception and experience of professional identity revealed in this study suggest a need to revise understandings of the role and identity of the professional musician in the context of contemporary portfolio careers in music. Using an explanatory sequential research design to combine data from a national survey of instrumental teachers with findings from eighteen individual case study interviews and one focus group, the research prioritises the lived experience of participants in generating understanding of professional lives and identities in this context.